Study on Machinability Issues of Hard to Machining Inconel 718 - A Review - Kishor K Powar,; Anupama N Kallol,; Shivakumar S,; Manjunath G Avalappa,; Balachandra P,; Nikhil Rangaswamy, (Malaysian Journal of Science, 2025)
In the aerospace and automobile industries, there has been a recent growing demand for tough and heat-resistant materials. Processing these materials is difficult, primarily due to their mechanical properties, which include strong wear resistance, abrasion resistance, and low heat conductivity. This results in short tool lifetimes and high cutting temperatures and forces. Variations in machinability may be brought on by changes in material microstructures brought on by changes in chemical composition, forging methods, casting, and heat treatment. Because of their remarkable greater efficiency and effectiveness, Inconel 718 nickel superalloys are employed in numerous automotive, marine, and aviation applications. In contrast, Inconel 718's poor thermal conductivity and quick strain hardening made fabrication difficult and compromised the surface's machining ability. This study examines Inconel 718 machining problems, and the issue of dry machining and machining with nanofluids, which demonstrates advancements in research on improving surface quality and material removal rate by reviewing the properties of alumina (Al2O3)-based nanofluids.